The WE-RISE™ multi-domain intervention: a feasibility study for the potential reversal of cognitive frailty in Malaysian older persons of lower socioeconomic status - Resshaya Roobini Murukesu; Suzana Shahar; Ponnusamy Subramaniam; Hanif Farhan Mohd Rasdi; Amrizal Muhammad Nur; Devinder Kaur Ajit Singh (BMC Geriatrics)
Abstract Background Cognitive frailty (CF) is an emerging concern among older persons, particularly within lower socioeconomic statuses (SES) populations. Currently, there is limited evidence on the potential reversibility of CF through multi-domain interventions within this demographic. This study aimed to investigate the effectiveness of the WE-RISE™ multi-domain intervention in addressing the potential reversibility of CF among community-dwelling older persons of lower SES, the intervention effects on multiple health dimensions, and to determine if WE-RISE™ is of low cost. Methods This 24-week randomised controlled trial included 55 community-dwelling older persons of lower SES with CF, who were randomised into either the WE-RISE™ intervention group (n = 27), or the control group receiving usual care (n = 28). The WE-RISE™ intervention comprised of 12 weeks of instructor led, community-based intervention, followed by 12 weeks of WE-RISE™@Home. CF status, cognitive and physical function, nutrition, disability, health-related quality of life, exercise self-efficacy and depression were assessed at baseline, 12th and 24th weeks. Changes in CF status was analysed descriptively, while intervention effects were analyzed with split plot ANOVA. The cost of the WE-RISE™ intervention was calculated using activity-based costing. Results At baseline, all participants in both the intervention and control groups (100%) were classified as CF. Following 12 weeks of the WE-RISE™ intervention, 74.1% of participants in the experimental group no longer met the criteria for cognitive frailty, with 63% maintaining this improvement at 24 weeks. In contrast, the CF status of participants in the control group remained largely unchanged, with only 10.7% showing improvement at 12 weeks and falling to 3.6% at 24 weeks. Significant intervention effects were observed for cognition, physical function, body composition, disability, health-related quality of life and self-perceived exercise self-efficacy (p < 0.05) following participation in WE-RISE™. The cost per intervention session was RM4.06 (≈ USD 0.90), and the cost per subject for 48 sessions was RM194.74 (≈ USD 43.39). Conclusion The WE-RISE™ multi-domain intervention has demonstrated potential in reversing CF among older persons of lower SES, leading to significant improvements across multiple health dimensions at a low cost. WE-RISE™ shows promise to enrich the well-being of ageing societies, contribute to societal health, and ensure equitable access to healthcare, supporting broader implementation by enhancing equitable access to health programs and addressing the needs of older persons, WE-RISE™. Trial registration This trial was registered in the Australian New Zealand Clinical Trials Registry (ACTRN12619001055190) on the 29th of July 2019 – retrospectively registered.